2022
DOI: 10.1186/s40001-022-00945-z
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose co-transporter 2 inhibitors in heart failure with mildly reduced or preserved ejection fraction: an updated systematic review and meta-analysis

Abstract: Objectives Heart failure with mildly reduced ejection fraction (HFmrEF)  or  heart failure with preserved ejection fraction (HFpEF)  are associated with significant morbidity and mortality, as well as growing health and economic burden. Sodium-glucose co-transporter 2 (SGLT2) inhibitors are very promising for the outcome improvement of patients with HFpEF or HFmrEF. The meta-analysis was performed to investigate the effects of SGLT2 inhibitors in HFpEF or  HFmrEF, by pooling data from all clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
11
0
3
Order By: Relevance
“…A recent meta-analysis reported similar findings to ours but it did not explore the benefit of SGLT2i in improving the quality of life of patients (30). Our study showed that SGLT2i significantly improve the quality of life based on KCCQ and MLHF questionnaires which is an important finding for patients who desire effective treatment options that can not only alleviate symptoms but also improve their overall well-being and day-today functioning.…”
Section: Ef Diagnostic Thresholdsupporting
confidence: 64%
“…A recent meta-analysis reported similar findings to ours but it did not explore the benefit of SGLT2i in improving the quality of life of patients (30). Our study showed that SGLT2i significantly improve the quality of life based on KCCQ and MLHF questionnaires which is an important finding for patients who desire effective treatment options that can not only alleviate symptoms but also improve their overall well-being and day-today functioning.…”
Section: Ef Diagnostic Thresholdsupporting
confidence: 64%
“…O objetivo deste estudo é contribuir para uma melhor compreensão das opções terapêuticas disponíveis e a avaliação do desfecho geral dessas terapias na gestão da insuficiência cardíaca. Wang et al, (2022) conduziram uma revisão sistemática atualizada e meta-análise que se concentrou na avaliação da eficácia dos inibidores do cotransportador de sódio-glicose 2 (SGLT2) em uma população específica de pacientes: aqueles com insuficiência cardíaca e fração de ejeção levemente reduzida ou preservada. Este estudo representou uma contribuição significativa para a literatura, pois abordou uma área emergente no tratamento da insuficiência cardíaca, destacando a promessa terapêutica dos inibidores do SGLT2 nesse subgrupo de pacientes.…”
Section: Metodologiaunclassified
“…Wang et al 97 en 2022 publicaron una RS que evaluó el impacto de los iSGLT-2 en pacientes con ICFEp y ICFEm. Los autores incluyeron 6 ECAs con 15,989 participantes.…”
Section: Revisión De La Literatura Y Análisisunclassified
“…Entre estos beneficios, la pérdida ponderal ha generado mucho interés por la importancia que tienen el sobrepeso y la obesidad en la fisiopatología de distintas enfermedades metabólicas y cardiovasculares. Una RS publicada recientemente por Wang et al 152 demostró que el tratamiento de pacientes con insuficiencia cardiaca con iSGLT-2 se asoció a una disminución ponderal significativa (DM -1.36 kg, IC95%: -1.68; -1.03) 152 .…”
Section: Revisión De La Literatura Y Análisisunclassified